EFFECTIVE STRATEGIES FOR TEACHING SYNONYMS AND ANTONYMS TO 6 TH GRADE LEARNERS OF ENGLISH - Xaydarova Shoira,; Anorboyeva Oydinoy Azizbek qizi, (TADQIQOTLAR, 2026)
Abstract: This work explores effective strategies for teaching synonyms and antonyms to 6th grade learners of English. The approach emphasizes the use of context clues, word maps, and matching games to help learners differentiate meanings and understand usage variations. Teachers guide students in recognizing subtle differences between words, supporting deeper semantic awareness. Activities such as sentence creation enhance learners’ ability to apply new vocabulary in both spoken and written communication. The use of thesaurus exploration and word families further expands students’  vocabulary  knowledge  and  promotes  independent  learning.  Continuous repetition,  practice,  and  integration  of  real-life  examples  ensure  retention  and appropriate  usage  of  synonyms  and  antonyms.  Overall,  these  strategies  create  an interactive  and  meaningful  learning  environment  that  strengthens  vocabulary development among 6th grade English learners.